The existence and persistence of household financial hardship: A Bayesian multivariate dynamic logit framework - Brown, Sarah; Ghosh, Pulak; Taylor, Karl (Journal of Banking & Finance, 2014)
We investigate the existence and persistence of financial hardship at the household level using data from the British Household Panel Survey. Our modelling strategy makes three important contributions to the existing literature on household finances. Firstly, we model nine different types of household financial problems within a joint framework, allowing for correlation in the random effects across the nine equations. Secondly, we develop a dynamic framework in order to model the persistence of financial problems over time by extending our multi-equation framework to allow the presence or otherwise of different types of financial problems in the previous time period to influence the probability that the household currently experiences such problems. Our third contribution relates to the possibility that experiencing financial problems may be correlated with sample attrition. We model missing observations in the panel in order to allow for such attrition. Our modelling framework allows us to identify any persistence in financial problems over time as well as any interdependence that may exist between different types of financial problems. Our findings reveal interesting variations in the determinants of experiencing different types of financial problems including demographic and regional differences. Our findings also highlight persistence in experiencing financial problems over time as well as the role that saving on a regular basis can play in mitigating current financial problems.